The cellular basis for animal regeneration - Tanaka, Elly (2011)
The ability of animals to regenerate missing parts is a dramatic and poorly understood aspect of biology. The sources of new cells for these regenerative phenomena have been sought for decades. Recent advances involving cell fate tracking in complex tissues have shed new light on the cellular underpinnings of regeneration in Hydra, planarians, zebrafish, Xenopus, and Axolotl. Planarians accomplish regeneration with use of adult pluripotent stem cells, whereas several vertebrates utilize a collection of lineage-restricted progenitors from different tissues. Together, an array of cellular strategies—from pluripotent stem cells to tissue-specific stem cells and dedifferentiation—are utilized for regeneration.